Legacy of drosophila genetics: female germline stem cells - Buszczak, Michael (Henry Stewart Talks, 2013)
Lineage tracing, Stem cell niches, Germline stem cell niche in ovary, Germline stem cell niche in testis, Dedifferentiation, Stem cell signaling back to the niche, Intestinal stem cells, Stem cell chromatin, Update interview: How ribosome biogenesis and mRNA translation impact germ cell differentiation, Update interview: Function of the differentiation factor bag of marbles (bam), Update interview: Chromatin factors, Update interview: Nuclear lamina, Update interview: DNA damage, Update interview: Niche signaling, Update interview: Regulation of niche size, Update interview: Single cell RNA-seq studies
Updated at 2021/04/25